DISEASE DETECTION EXPERT SYSTEM IN WATERMELON PLANTS USING CERTAINTY FACTOR METHOD BASED ON MOBILE - Juhartini, Juhartini; Arwidiyarti, Dwinita; Subki, Ahmad Subki (LPPM Universitas Nusa Mandiri, 2022)
Watermelon is one of the fruit commodities currently being developed in West Nusa Tenggara by making Central Lombok Regency as its production center. The problems that are often faced by farmers in watermelon farming, apart from pests, watermelon plants are also often affected by diseases that cause the plants to wilt and then dry, white spots on the flesh, the growth of leaves and small fruit so that it has an impact on decreasing productivity caused by lack of knowledge farmers in recognizing and dealing with diseases in watermelon plants so that they are often mishandled. This research was conducted with the aim of producing an expert system that can be used to detect diseases in watermelon plants and provide solutions for handling them so that watermelon farmers can make prevention and treatment efforts quickly before the disease is transmitted to many other watermelon plants. This expert system was built with the Mobile-based Certainty Factor Method with the Android operating system so that it can be downloaded in the Playstore by watermelon farmers or anyone who needs it so that it is expected to help farmers detect diseases in watermelon plants and provide appropriate handling steps based on related theories.